From Reverence to Rape / The Treatment of Women in the Movies - Haskell Molly (The University Of Chicago Press, 1987)
From Reverence to Rape is an incisive, exceedingly thoughtful look at the distorted lens through which Hollywood has historically viewed women. Preface, Acknowledgements, Introduction, The Big Lie, The Twenties, The Thirties, The Woman's Film, The Forties, The Fifties, The Europeans, The Sixties, 1974-1987: The Age of Ambivalence, Index.